Exploring the potential of a Ephedra alata leaf extract: Phytochemical analysis, antioxidant activity, antibacterial properties, and green synthesis of ZnO nanoparticles for photocatalytic degradation of methylene blue - Zaater, Abdelmalek; Serhoud, Mohammed Oualid; Ben Amor, Ilham; Zeghoud, Soumeia; Hemmami, Amira; Rebiai, Abdelkrim; Bouras, Yacine; Laiche, Ammar Touhami; Alsalme, Ali; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Ephedra alata leaf extracts have therapeutic properties and contain various natural compounds known as phytochemicals. This study assessed the phytochemical content and antioxidant effects of a Ephedra alata leaf extract, as well as zinc oxide (ZnO) nanoparticle production. The extract contained phenolic acids, including vanillic acid, chlorogenic acid, gallic acid, p-coumaric acid, vanillin and rutin. Its total phenolic content and total flavonoid content were 48.7 ± 0.9 mg.g-1 and 1.7 ± 0.4 mg.g-1, respectively. The extract displayed a DPPH inhibition rate of 70.5%, total antioxidant activity of 49.5 ± 3.4 mg.g-1, and significant antimicrobial activity toward Gram-positive and negative bacteria. The synthesized ZnO nanoparticles had spherical shape, crystallite size of 25 nm, particle size between 5 and 30 nm, and bandgap energy of 3.3 eV. In specific conditions (90 min contact time, pH 7, and 25°C), these nanoparticles efficiently photodegraded 87% of methylene blue, suggesting potential applications for sustainable water treatment and pollution control.